Analysis of School Grouping Against Educational Teachers in NTB Using K-Prototypes Method - Gloria Milenda Jesika Prima; Charitas Fibriani (Universitas Bina Darma, 2022)
The shortage of teaching staff is still a problem in education in Indonesia, resulting in the number of teachers and students being unbalanced. It is very significant based on data from the Analysis of the Distribution of Teachers in Region 3T, which shows that the national ratio of teachers per school is 18.41, and many still have a ratio of teachers per school lower than the national. Therefore, it is necessary to group the data in one of the 3T regions, especially in the Province of West Nusa Tenggara (NTB). The data used for this study were 4997 schools from 8 districts and two cities. The results of this study were conducted to determine whether the grouping ratio of the number of teachers and students is ideal or not ideal. The data used are categorical and numeric data types, so the clustering analysis method used is K-Prototypes. Each cluster produces a different range of teachers and students. Cluster 1, which obtained the High category almost followed the ideal, while Cluster 2 and the Cluster 3 were still far from ideal. This needs to be considered to increase the number of teaching staff in the Education Office in each district.